End-binding protein 1 stimulates paclitaxel sensitivity in breast cancer by promoting its actions toward microtubule assembly and stability. Issue 6 (19th April 2014) - Luo, Youguang; Li, Dengwen; Ran, Jie; Yan, Bing; Chen, Jie; Dong, Xin; Liu, Zhu; Liu, Ruming; Zhou, Jun; Liu, Min
Abstract: Paclitaxel is a microtubule-targeting agent widely used for the treatment of many solid tumors. However, patients show variable sensitivity to this drug, and effective diagnostic tests predicting drug sensitivity remain to be investigated. Herein, we show that the expression of end-binding protein 1 (EB1), a regulator of microtubule dynamics involved in multiple cellular activities, in breast tumor tissues correlates with the pathological response of tumors to paclitaxel-based chemotherapy. In vitro cell proliferation assays reveal that EB1 stimulates paclitaxel sensitivity in breast cancer cell lines. Our data further demonstrate that EB1 increases the activity of paclitaxel to cause mitotic arrest and apoptosis in cancer cells. In addition, microtubule binding affinity analysis and polymerization/depolymerization assays show that EB1 enhances paclitaxel binding to microtubules and stimulates the ability of paclitaxel to promote microtubule assembly and stabilization. These findings thus reveal EB1 as a critical regulator of paclitaxel sensitivity and have important implications in breast cancer chemotherapy.